2018
DOI: 10.1093/ofid/ofy260
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Validation of a Commercial LAMP Test for Ruling out Malaria in Returning Travelers: A Prospective Diagnostic Trial

Abstract: The mainstay of malaria diagnosis relies on rapid diagnostic tests (RDTs) and microscopy, both of which lack analytical sensitivity. This leads to repeat testing to rule out malaria. A prospective diagnostic trial of the Meridian illumigene Malaria assay (loop-mediated isothermal amplification [LAMP]) was conducted comparing it with reference microscopy and RDTs (BinaxNOW Malaria) in returning travelers between June 2017 and January 2018. Returning travelers with signs and symptoms of malaria were enrolled in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 29 publications
(29 reference statements)
3
30
0
Order By: Relevance
“…Since NAATs diagnostic methods are more sensitive and have a lower limit of parasite detection than RDTs and microscopy, discrepancies are expected in the results obtained by NAATs and other diagnostic methods. Previous studies have reported a limit of detection of < 6 parasites/µL for NAATs compared to 100-200 parasites/µL for RDTs and 50 parasites/µL for microscopy [12,38]. The sensitivity of MG-LAMP was higher than RDT and microscopy, but a lower specificity at the two health facilities.…”
Section: Discussionmentioning
confidence: 84%
“…Since NAATs diagnostic methods are more sensitive and have a lower limit of parasite detection than RDTs and microscopy, discrepancies are expected in the results obtained by NAATs and other diagnostic methods. Previous studies have reported a limit of detection of < 6 parasites/µL for NAATs compared to 100-200 parasites/µL for RDTs and 50 parasites/µL for microscopy [12,38]. The sensitivity of MG-LAMP was higher than RDT and microscopy, but a lower specificity at the two health facilities.…”
Section: Discussionmentioning
confidence: 84%
“…Limitations to identify infections with low parasitemia can be overcome by PCR that can detect <5 parasites/μl [8,9,17,18]. LAMP also has an adequate analytical sensitivity to detect low parasite-level parasitemia, compared to PCR [7,10,11].…”
Section: Discussionmentioning
confidence: 99%
“…The illumigene ® malaria test is a simple and rapid molecular diagnostic test allowing its integration into a 24/7 routine workflow. Because of a simplified sample preparation step and ready-to-use reagents, no technical expertise in molecular biology is needed and the results can be obtained within 1 h. In a recent study, both sensitivity as well as specificity of LAMP was found to be 100% versus microscopy when discrepant results were resolved using PCR [11]. Therefore, the illumigene ® malaria test represents a useful and cost-effective tool for emergency diagnostics [6,7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations